1996
DOI: 10.1111/j.1399-3089.1996.tb00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Gal‐α1,3‐Gal epitope expression in transgenic mice expressing human H‐transferase

Abstract: There is now considerable evidence implicating anti‐Gal xenoantibodies as a key instigator in the hyperacute rejection of discordant xenografts. As a consequence it is generally held that elimination or reduction of the Gal/anti‐Gal component is critical to overcoming hyperacute rejection. We have recently shown that in mice inactivation of the GalT gene by homologous recombination completely eliminates the expression of the Gal‐epitope and that hearts from these mice demonstrate prolonged survival when perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 16 publications
3
27
0
Order By: Relevance
“…Similar numbers of the dense granules that contain adenine nucleotides were present in both (data not shown). Consistent with our previous results using the H-2K b promoter (24,25), transgene expression was widespread in all tissues examined, including heart, lung, and pancreas, and was particularly strong on endothelium ( Figure 1B). Correct processing of hCD39 in the tissues of transgenic mice was confirmed by Western blot analysis ( Figure 1C).…”
Section: Resultssupporting
confidence: 80%
“…Similar numbers of the dense granules that contain adenine nucleotides were present in both (data not shown). Consistent with our previous results using the H-2K b promoter (24,25), transgene expression was widespread in all tissues examined, including heart, lung, and pancreas, and was particularly strong on endothelium ( Figure 1B). Correct processing of hCD39 in the tissues of transgenic mice was confirmed by Western blot analysis ( Figure 1C).…”
Section: Resultssupporting
confidence: 80%
“…As part of our xenotransplantation program, we generated hFUT1 transgenic mice expressing human α1,2‐fucosyltransferase , also known as H‐transferase (HTF) because it is responsible for the synthesis of H substance (blood group O). The rationale for this strategy was that HTF reduces the expression of the major porcine xenoantigen galactose‐α1,3‐galactose (αGal) by competing for the substrate of α1,3‐galactosyltransferase .…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicate that there is no direct competition between mouse α1,3GT and human α1,2fucosyltransferase or α2,3sialyltransferase, which are more or less expressed in parental BxPC‐3 and Panc‐1 cells,16 for the same acceptor substrate. Many studies on the hyperacute rejection of xenografts have shown a reduction of the level of αGal epitope in transgenic mice and pigs due to the expression of an α1,2fucosyltransferase,42, 43, 44, 45 suggesting that α1,2fucosyltransferase activity could be dominant over that of the α1,3GT in the Golgi subcompartmentation. These data corroborate results reported by Osman et al 46.…”
Section: Discussionmentioning
confidence: 99%